Duifhuis pitch: neuromagnetic representation and auditory modeling - Andermann, Martin; Rupp, André (Journal of neurophysiology, 2014)
When a high harmonic is removed from a cosine-phase harmonic complex, we hear a sine tone pop out of the perception; the sine tone has the pitch of the high harmonic, while the tone complex has the pitch of its fundamental frequency, f0. This phenomenon is commonly referred to as Duifhuis Pitch (DP). This paper describes, for the first time, the cortical representation of DP observed with magnetoencephalography. In experiment 1, conditions that produce the perception of a DP were observed to elicit a classic onset response in auditory cortex (P1m, N1m, P2m), and an increment in the sustained field (SF) established in response to the tone complex. Experiment 2 examined the effect of the phase spectrum of the complex tone on the DP activity: Schroeder-phase negative waves elicited a transient DP complex with a similar shape to that observed with cosine-phase waves but with much longer latencies. Following the transient DP activity, the responses of the negative and positive Schroeder-phase waves converged, and the increment in the SF slowly died away. In the absence of DP, the two Schroeder-phase conditions with low peak factors both produced larger SFs than cosine-phase waves with large peak factors. A model of the auditory periphery that includes coupling between adjacent frequency channels is used to explain the early neuromagnetic activity observed in auditory cortex.